THE OLYMPIC 2020 AGENDA IN THE CONTEXT OF THE UNITED ARAB EMIRATES (Fiep Bulletin - online, 2019)
This paper will cover a brief discussion of the Olympic Agenda 2020 created by the International Olympic Committee(IOC) to address current challenges the Olympic Movement is facing and to improve the future of the Olympic Games. First, aquick introduction will briefly present the Agenda 2020 and the details of its creation. Then a short explanation of each of the 40recommendations will be covered. Finally, an analysis of Agenda 2020 within the local context of the UAE will be covered and howthe country can benefit from such recommendations by the IOC.